PENGARUH SIKLUS HIDUP DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2009-2011) - Anggraini, Anggi Ratna (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research is aimed to examine the effect of corporate life cycles (growth, mature, and stagnant) and firm size (small, medium, big) to earnings management. This earnings management differences were shown by the magnitude of earnings management in every life cycle stage and firm size. Small-sized firms and may have not sophisticated internal control system engage in more earnings management, as measured by discretionary accrual. Firm in mature and stagnant stage may have more sophisticated internal control system than firm in growth stage. The sample of the study was the manufacturing companies listed in the Indonesia Stock Exchange. The data observation period was 3 years (2009-2011). The data was collected using purposive sampling method. Total samples were 252 firms, consist of 84 corporate each year. Earnings management was indicated by the magnitude of discretionary accruals. The samples are classified into various life cycle using dividend payout, sales growth, and age. Firm size are classified by total assets. As predicted, the empirical results indicate firms in growth, mature, and stagnant stage are conducting earnings management. This research could found earnings management differences between firm size, but not between corporate life cycle. Next similar research should use more sample data in longer period and use four or five classification of corporate life cycle to get more powerful result and more detail to examine it’s effect on earnings management. Keywords: earnings management, corporate life cycle, growth, mature, stagnant, firm size, small, medium, big